Vaginal epithelioid trophoblastic tumor mimicking vaginal fistula: a case report and literature review - Li, Dong-mei; Yu, Xiu-zhang; Qie, Ming-rong; Duan, Rui-qi (Frontiers in Oncology, 2025)
BackgroundEpithelioid trophoblastic tumor (ETT) is a rare variant of gestational trophoblastic neoplasia. This article presents a case of vaginal ETT, initially misdiagnosed as vaginal carcinoma, in a patient with no history of gestational trophoblastic disease. The aim is to explore the clinical characteristics and diagnostic features of this condition.Case presentationA 50-year-old woman presented with a 3-year history of vaginal pain. Following a vaginal fistula repair at an external hospital, a biopsy unexpectedly revealed vaginal carcinoma, prompting referral to our institution for further management. Pathological examination confirmed a diagnosis of extremely rare vaginal ETT, with immunohistochemistry showing characteristic marker positivity. Notably, the patient had no history of gestational trophoblastic disease, and serum Human Chorionic Gonadotropin (HCG) levels remained normal throughout. After diagnosis, the patient underwent total hysterectomy, bilateral salpingo-oophorectomy, and partial vaginectomy. Postoperative pathology confirmed the primary site to be the vagina, an unusual location for ETT. To further control the disease, the patient received 6 cycles of EMA-CO chemotherapy. Follow-up at 1 year showed no recurrence or metastasis, with stable disease.ConclusionETT often present with nonspecific symptoms, which can lead to misdiagnosis. Vaginal delivery and induced abortion may be potential risk factors. Clinically, in patients presenting with vaginal pain, masses, or genital tract fistulas, the possibility of a trophoblastic tumor should be considered and thoroughly evaluated.